De la promesa de salvación a la religión tecnológica: milenarismo y mesianismo en las raíces de la tecnología moderna (2021)
The objective of this article is to introduce a historical understanding of the relationship between millennialism and modern technology. Traditionally, this relationship has been described from the dialectical concept of ‘secularization’, the notion of ‘technology’ as domination of the human being over nature and the Catholic notion of mitigated millenarianism’. We will point out some limitations that these notions impose on a historical understanding of the technological phenomenon, since they ignore their participation in the historical processes of value creation. We propose a genealogical explanation of the persistence of belief in the promise of salvation in technological culture, denouncing the dialectical notion of "secularization" and offering broader descriptions of "millennialism" and "technology".